Ta’awun and Marketing Agility of Firm Survivors - Sulhaini; Sagir, Junaidi; Sulaimiah (International Journal of Islamic Business and Economics (IJIBEC), 2023)
This study’s objective is to examine a model to shed light on what factors affect the marketing agility of SME survivors. Data was collected from SME survivors spread across five different districts on the island of Lombok, Indonesia. The sample firms were purposively selected; they were survivors of the pandemic with Muslim owners or managers. According to the study, knowledge assets strengthen marketing agility, but market turbulence does not moderate the effect. Regardless of market conditions, SMEs always use their assets to maintain agility and resilience. In addition, internal human resource practices generate favorable atmospheres for internal learning. While ta’awun facilitates the transfer of knowledge from partners, this knowledge is further developed internally where employees have been prepared through internal practices. The practices and ta’awun become the keys to strengthening SMEs’ knowledge assets. However, older company age does not strengthen the influence of knowledge assets on marketing agility. Conversely, the older the company, the more difficult it is to develop and utilize knowledge assets to innovate and quickly adapt to market developments.